Modeling of the dynamics of tornado structures in a pipe with turbulators of square, semicircular and triangular profiles - I. E. Lobanov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. To carry out mathematical simulations of changes in time of tornado compositions in channels with projections of semicircular, triangular, square profiles for average Reynolds criteria based on multiblock computing technology with the solution of finite- volume factorized methods of the Reynolds equation and energy equations.Method. The calculations were carried out on the basis of theoretical approaches based on the solution of Reynolds equations by finite-volume factorized methods, which were closed using the simulation of Menter stresses, and the energy of a structured grid.Result. The calculations of time-dependent flow and heat transfer parameters carried out in the article showed that the excess dissipation of turbulence generation for projections of sharp profiles - square profile, triangular profile - and rounded profiles - semicircular profile, segment profile - is provided with radically different hydraulic losses: channels with protrusions of rounded profiles, for example, semicircular, have much lower hydraulic resistance coefficients than channels with protrusions with sharp profiles, for example, triangular or square, rectangular.Conclusion. In the article, mathematical simulations of time-dependent tornado compositions were performed in channels with transversal profiles in the form of a square, triangle and semicircle, which is as informative as possible in terms of studying turbulent flows and heat transfer arising under average Reynolds criteria based on computer multiblock technology when using solutions of finite-volume factorized methods (FCOM-am) Reynolds equations and energy equations. The following protrusions were considered in the article: square transversal profiles, in which tornadoes are most pronounced, and side tornadoes affect the flow in the maximum way; triangular transversal profiles, where tornadoes are not so strong, and side tornadoes affect the main flow weaker than with square protrusions; semicircular transversal profiles, in which the incoming main tornado moves along the stream with the generation of limited side tornadoes. The calculated information obtained in the article correlates to a high degree with the available experimental data, which indicates the verification of the mathematical modeling involved in the article.